Effects of probiotics on performance of chickens under normal and heat-stress conditions - Abdlzahera, Yassir Wesam (2016)
Poultry industry in most developing and newly developed countries in Asia is highly depending on importation of cheap feed ingredients at the sacrifice of quality. In view of the severe restriction or total ban on the use of antibiotics as growth promoters in livestock and poultry production, probiotic has been suggested as an alternative to antibiotics to promote productivity. Probiotic is a live microbial feed supplement which improves intestinal microbial balance and thus feed utilization and overall health of the host animal. Heat stress is one of the significant environmental challenges affecting poultry production all over the world, particularly in the tropics. Animals are considered to be under heat stressed if they have difficulty to achieve a balance between body heat production and body heat loss. The overall objective of this study was to investigate the probiotic efficacy of mixture of two strains of Lactobacillus, namely L. pentosus ITA23 and L. acidipiscis ITA44 which were isolated from local Mulberry (Morus alba) silage on stress reduction of broiler chickens kept under hot environment. Two experiments were conducted to test the hypothesis that probiotic can effectively reduce stress and thus sustain productivity in chickens kept under hot environment. The first experiment was conducted under ambient temperature in an open-sided poultry experimental house to examine the effect of the probiotic on performance, cecal bacterial population and relevant blood parameters in chickens. One hundred twenty day-old broiler chicks (Cobb500) were randomly allocated into two dietary treatments; commercial diet (control) and commercial diet supplemented with probiotic (1g /kg diet) in a 35-day feeding trial. Results showed that although there were no differences (P>0.05) in average daily weight gain (ADG), birds supplemented with probiotic had more efficient feed conversion ratio (FCR) compared to those without probiotic supplementation. The supplementation of the two strains of Lactobacillus tends to lower concentrations of serum total cholesterol, low density lipoprotein (LDL) and triglyceride, they were not significantly different with those in the control group. The second experiment was carried using 192 day-old chicks (Cobb500) to examine the effect of probiotic supplementation on broiler chickens under heat-stress condition .The birds were randomly allocated in equal number to two dietary groups similar to that in Experiment 1 and kept under ambient temperature for the first two weeks. On day-15, birds in each dietary group were randomly divided into two subgroups and transferred to temperature-control chambers; one subgroup from each dietary group to 25°C (low temperature) and the remaining half to 35°C (high temperature) for the next three weeks. The results showed that birds kept in the low temperature chamber had higher ADG than those in the high temperature groups, and supplementation of probiotic reduced the negative effect of high temperature on ADG of birds. Similarly, high temperature negatively affected FCR and probiotic supplementation improved FCR, with birds supplemented with probiotics in the low temperature group had the most efficient FCR while those without probiotic supplementation in the high temperature recorded the least efficient FCR. Supplementation of the two strains of Lactobacillus did not alter total gut microbial population under both temperature conditions, but probiotic supplementation significantly (P<0.05) increased population of the beneficial bacteria (Lactobacillus, Bifidobacter and Entrocucous) in the cecum samples. However, probiotics only reduced population of pathogen (Entrobacter and E. coli) in the cecum samples of broilers kept under low temperature but not in those under high temperature. Results of this study suggested that supplementation of the two strains of probiotic bacteria improved FCR. This could be because of the healthier gut environment as shown by the higher population of beneficial bacteria in cecum of birds fed probiotic as well as the higher antioxidant activity of these birds to cope with stress associated with high temperature.